Pengembangan Perangkat Pembelajaran Berbasis Technological Pedagogical And Content Knowledge (TPACK) Bagi Guru IPA Dan IPS Di DIY - Dyah Purwaningsih; Anik Widiastuti, S.Pd., M.Pd.; Pujianto Pujianto; M Dihan; N Alfiana (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2023)
This PKM project aims to improve teacher competence in learning through TPACK training for science and social studies teachers in the Province of DIY. This program was carried out online from April to October 2021 with 65 science and social studies teachers participating. The implementation of PPM activities is divided into five stages, namely the first delivery of material, information-discussion, assignment and training, mentoring and monitoring, implementation and evaluation of activities. The result of implementing the program is that participants gain an understanding of learning tools, have the skills to develop their learning tools and increase motivation in developing their learning tools based on TPACK